Analysis of Educational Resource Allocation Strategy: A Case Study on Budget Management - Hidayah, Neneng Nur; Pulungan, Desriyanti (Lembaga Riset Mutiara Akbar, 2024)
To ensure the learning process takes place, financing management is needed which is used as a reference in managing and allocating education funds. Sources of funds originating from the central, regional and community sources of funds must be used effectively in order to achieve educational goals. Education funds must be accountable for their use in accordance with the priority scale needed for the sustainability of the quality of education which correlates with the cost of education. It is hoped that proper management and allocation of education funds will be able to address the need for funds which are a prerequisite for a quality learning process.